2011
DOI: 10.1007/s00125-011-2319-x
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous ABCC8 mutations are a cause of MODY

Abstract: Aims/hypothesis The ABCC8 gene encodes the sulfonylurea receptor 1 (SUR1) subunit of the pancreatic beta cell ATP-sensitive potassium (K ATP ) channel. Inactivating mutations cause congenital hyperinsulinism (CHI) and activating mutations cause transient neonatal diabetes (TNDM) or permanent neonatal diabetes (PNDM) that can usually be treated with sulfonylureas. Sulfonylurea sensitivity is also a feature of HNF1A and HNF4A MODY, but patients referred for genetic testing with clinical features of these types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(105 citation statements)
references
References 10 publications
1
101
0
3
Order By: Relevance
“…Активирующие же гомо-или гетерозиготные, а также компаунд-гетерозиготные мутации (в дан-ном случае мутантный ген может содержать как ак-тивирующую, так и инактивирующую аллели [24]) являются причиной неонатального СД. Клиниче-ски MODY12 сопоставим с MODY1 и 3; пациенты чувствительны к препаратам сульфонилмочевины [25]. Наш пациент на момент молекулярно-генети-ческого исследования получал терапию метформи-ном, в связи с чем ему была рекомендована госпи-тализация для решения вопроса о модификации терапии.…”
Section: Discussionunclassified
“…Активирующие же гомо-или гетерозиготные, а также компаунд-гетерозиготные мутации (в дан-ном случае мутантный ген может содержать как ак-тивирующую, так и инактивирующую аллели [24]) являются причиной неонатального СД. Клиниче-ски MODY12 сопоставим с MODY1 и 3; пациенты чувствительны к препаратам сульфонилмочевины [25]. Наш пациент на момент молекулярно-генети-ческого исследования получал терапию метформи-ном, в связи с чем ему была рекомендована госпи-тализация для решения вопроса о модификации терапии.…”
Section: Discussionunclassified
“…Mutations in ABCC8 have been previously identified in individuals diagnosed with MODY [122,123]. Other groups have reported that individuals with congenital hyperinsulinemia due to inactivating ABCC8 mutations eventually developed early-and adult-onset diabetes [124,125].…”
Section: A Loss-of-function Mutation In Abcc8 Increases the Risk For mentioning
confidence: 99%
“…More common forms such as GCK, HNF1A, and HNF4A comprise the majority of MODY cases [1][2][3][4][5][6][7][8][9]. Genetic testing for MODY has become a challenge, especially for rarer subtypes and for the completeness of mutation screening using traditional methods, either Sanger sequencing or multiplex ligation-dependent probe amplification (MLPA) [10].…”
Section: Introductionmentioning
confidence: 99%